O eletromagnetismo ensinado através da construção e aplicação de experimentos - Silveira, Luiz Gustavo Teixeira da (2018)
A Vergnaud’s Theory of Conceptual Fields was used to evaluate cognitive development due to the application of experiments of low cost within the context of Eletromagnetism for studentes in the Third Grade of High School of the State School Sant'Ana. The experiments are designed and applied for the Van der Graf generator, with PET bottles and a representative model of a Hydrometer. It was still applied a computational simulation, gives platform PHET, for assembly of electrical circuits. In general, a technical and scientific linguage allied to or learned two basic concepts of eletromagnetism foi bem unfolded in the classes A and B, classes to which the experiments were applied. Another characteristic is that we have a good idea of how we apply our applied tests in the classroom. In the meantime, to class C, class to which it is applied or traditional method, it has to work in all aspects when compared to other turmas. This performance is revealed to numerous factors such as: lack of interest, difficulty in discipline, lack of mathematical and linguistic basis, and a contextualization of discipline not on a day-to-day basis. I do not point out the Theory of Conceptual Fields, or fact of the classes A e B have a good income and allied to or protagonism of student in the teaching-learning process, making the teacher were just a mediator of this process. Another analyze was related to the resolution of exercices, by the second Vergnaud, this practice and of great importance for the apprenticeship of the non-ensino of Mathematics and Physics. However, the class C, even with the resolution of numerous exercises solved, showed a below-expected yield when compair with another class. This should, mainly, to mechanization of solving exercises by having the student so that the student does not think about the physical and mathematical concepts involved but use the reminder that you have solved some other similar exercise. This fator is effective, I do not put of sight of "passing year " and college entrance exams, but, and ineffective when it comes to actually learning the physical concept in the matter.